Physical therapist management and coordination of care to prevent pathological hip fracture from metastatic disease: a case report - Athena Manzino; Christopher Wilson; Christopher Wilson (Frontiers Media S.A., 2024)
BackgroundBone metastases are common in patients with progressive cancer and often present in long bones, leading to adverse events such as pathologic fractures. In the acute care setting, physical therapists (PTs) may be the initial providers who identify symptoms associated with fracture risk and communicate concerns to help prevent such adverse events.Case descriptionA 39-year-old female patient with metastatic breast cancer was admitted to the hospital due to uncontrolled pain. She had a history of bone metastases to the left femur; however, no restrictions or precautions were noted during the initial PT examination. During this initial PT examination, she reported worsening hip pain with weight-bearing activities.OutcomesWith the PT's recognition of red flag symptoms, an MRI was completed, which revealed extensive metastatic disease in her left femur with concern for an imminent fracture; as a result, prophylactic fixation was performed. Her functional abilities improved after surgery and consistent therapeutic intervention, allowing her to achieve a level of independence sufficient to return home safely.Discussion and conclusionThis case demonstrates the successful identification of imminent fracture risk by a PT in a patient with metastatic breast cancer, as well as the therapeutic management that accompanied this process in the acute care setting.